A Disaster Management Framework Using Internet of Things-Based Interconnected Devices. (20th May 2021) - Sharma, Kaljot; Anand, Darpan; Sabharwal, Munish; Tiwari, Pradeep Kumar; Cheikhrouhou, Omar; Frikha, Tarek
Abstract : The advanced technology Internet of Things (IoT) visualizes a worldwide, that is, internally connected, networks of smart physical entities. IoT is a promising technology used in several applications including disaster management. In disaster management, the role of IoT is so important and ubiquitous and could be life-saving. This article describes the role of IoT in disaster management. More precisely, it presents IoT-based disaster management for different kind of disasters with a comparison between some solutions that are available in the market. It shows an implementation of some examples of the application of IoT such as early-warning system for fire detection and earthquake and represents some approaches talking about the application, IoT architecture, and focusing of the study on different disasters. This study could be a good guide to stakeholder about the use of IoT technology to secure their smart cities' infrastructure and to manage disaster and reduce risks.